Morphological Properties of Gastropod Shells in a Warmer and More Acidic Future Ocean Using 3D Micro-Computed Tomography - Chatzinikolaou, Eva; Keklikoglou, Kleoniki; Grigoriou, Panos (Frontiers in Marine Science, 2021)
The increased absorption of atmospheric CO2 by the ocean reduces pH and affects the carbonate chemistry of seawater, thus interfering with the shell formation processes of marine calcifiers. The present study aims to examine the effects of ocean acidification and warming on the shell morphological properties of two intertidal gastropod species, Nassarius nitidus and Columbella rustica. The experimental treatments lasted for 3 months and combined a temperature increase of 3°C and a pH reduction of 0.3 units. The selected treatments reflected the high emissions (RCP 8.5) “business as usual” scenario of the Intergovernmental Panel on Climate Change models for eastern Mediterranean. The morphological and architectural properties of the shell, such as density, thickness and porosity were examined using 3D micro-computed tomography, which is a technique giving the advantage of calculating values for the total shell (not only at specific points) and at the same time leaving the shells intact. Nassarius nitidus had a lower shell density and thickness and a higher porosity when the pH was reduced at ambient temperature, but the combination of reduced pH and increased temperature did not have a noticeable effect in comparison to the control. The shell of Columbella rustica was less dense, thinner and more porous under acidic and warm conditions, but when the temperature was increased under ambient pH the shells were thicker and denser than the control. Under low pH and ambient temperature, shells showed no differences compared to the control. The vulnerability of calcareous shells to ocean acidification and warming appears to be variable among species. Plasticity of shell building organisms as an acclimation action toward a continuously changing marine environment needs to be further investigated focusing on species or shell region specific adaptation mechanisms.